Light Pollution in the City of Zagreb, December 2010 Through July 2011 (Rudarsko-geološko-naftni zbornik, 2022)
Light pollution can be defined as an increase in the amount of the light levels in theenvironment caused by the human activity. Although a part of the electromagnetic spectrum just as e.g. microwaves orUV radiation, visible light has been, until recently, treated as completely harmless and without any significant impact onthe environment.From early 1960s onward, both science and society slowly begun to acknowledge the fact that light influences a largenumber of living organisms: plants, animals, and humans alike, in rather unsuspecting ways. It has been noticed as well,that poorly constructed outdoor light fittings allow the light to escape into the environment, outside of the target area.The term "light pollution" has been coined to describe the effect, that influences both ecology and economy of a region.Various methods of measurement can be used in order to assess the magnitude of light pollution effect, e.g. measuringdirect illumination in the vicinity of the sources, remote sensing via satellite imagery, measuring the amount of lightescaping the Earth's surface and measuring the sky brightness as observed from the Earth's surface. The research groupat the Faculty of Mining, Geology and Petroleum Engineering, University of Zagreb, chose the third method, makinguse of the Unihedron's Sky Quality Meter (SQM-LE). The goal of this first measurement period was to test theequipment, to obtain the preliminary data and to define the data processing methods. Measurements were collected atnight during eight months. Following conclusions can be drawn from this experiment:1. Measured values vary, strongly depending on atmospheric conditions. Main contribution to this variability comesfrom the water vapour and/or aerosol content in the atmosphere in the absence of clouds, or from the characteristics ofthe cloud layer above the SQM instrument in case of cloudy weather, water vapour being a rather efficient at reflectingand dispersing visible light. (The atmospheric conditions were assesed from the recordings obtained from the CroatianMeteor Network's camera mounted next to the SQM-LE instrument. This camera records the night sky in search of themeteor trails. Since all recorded frames and events are time-stamped, matching these with SQM-LE readings wasstraightforward.)2. Measured values fall into the interval [14 , 18.5] mag/arcsec 23. Values can be expected to converge to:i) 17 mag/arcsec 2 on average during springtime (on clear nights)ii) between 18 and 17 mag/arcsec 2  on average, during winter (on clear nights)iii) between16 and 15 mag/arcsec 2  , on average, during cloudy nights, regardless of season, depending on the height ofthe bottom of the cloud layer and the cloud densityFurther measurements are needed to get more accurate results as well as to extract any patterns or trends from the data.Also, the values obtained by measurements need to be input into models if the magnitude and the extent of lightpollution in Zagreb area is to be monitored.